2013
DOI: 10.1159/000357772
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib Enhances the Antitumor Activity of CPT-11 in vitro and in vivo by Inhibiting ABCG2 but Not ABCB1: A New Clue to Circumvent Gastrointestinal Toxicity Risk

Abstract: Background: Despite the potent antitumor activity of CPT-11, late-onset diarrhea owing to enterohepatic circulation of SN-38 is a critical issue. Methods: We aimed to evaluate the inhibitory potency of gefitinib against the ABCB1- or ABCG2-mediated excretion of CPT-11 and its active metabolite SN-38 in vitro and in vivo. Results: Gefitinib dose-dependently enhanced the antiproliferation activity of SN-38 in vitro by inhibiting ABCG2. The inhibitory effect of gefitinib on ABCB1 was marginal. When both CPT-11 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Although it was initially used as a monotherapy, it was shown that gefitinib has potential to reverse resistance when combined with various P-gp substrates, DOX, PTX, docetaxel, vincristine and cisplatin [24][25][26][27]. Its MDR reversing effect considerably depends on the applied concentrations, ranging from no or partial effect when applied in low doses [24,28] to moderate or pronounced effect when used in clinically relevant or high doses [24,25]. Similar to other TKIs, it directly interacts with P-gp and inhibits its function.…”
Section: Egfr Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Although it was initially used as a monotherapy, it was shown that gefitinib has potential to reverse resistance when combined with various P-gp substrates, DOX, PTX, docetaxel, vincristine and cisplatin [24][25][26][27]. Its MDR reversing effect considerably depends on the applied concentrations, ranging from no or partial effect when applied in low doses [24,28] to moderate or pronounced effect when used in clinically relevant or high doses [24,25]. Similar to other TKIs, it directly interacts with P-gp and inhibits its function.…”
Section: Egfr Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…In recent years, there have been many reports of interactions between ABCG2 and tyrosine kinase inhibitors [1,8,9]. Gefitinib and erlotinib are epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKIs) that are substrates of ABCG2 [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, EGFR TKIs have been reported to inhibit the transport of other substrates by ABCG2, suggesting that drug interactions may occur in patients taking these anticancer agents. Recently, we found that gefitinib inhibits both ABCB1 and ABCG2, and that the antitumor activity, tumor tissue, and blood concentrations of SN-38 (the active metabolite of irinotecan) are increased in tumor-bearing mice by administration of gefitinib in combination with irinotecan [9].…”
Section: Introductionmentioning
confidence: 99%